ANALISIS TATA RUANG (ZONASI) PENGEMBANGAN EKOWISATA DI KAWASAN TAMAN NASIONAL BALURAN JAWA TIMUR - Mukhammad Muryono (The East Java Biological Society, 2011)
Research on potential ecotourism development at Baluran National Park which consists more than 25.000 Hectares area and coast line about 42 km long has been conducted from June to September 2003 in the local communities area around Baluran National Park and 5 ecosystems type such as mangrove forest, lowland tropical forest, deciduous forest, evergreen forest, and grassland. The objectives of this study were to definited the zonation for ecotourism. For these, research was initiated to inventory ecotourism supply such are biophysic attractions, socio culture local people attractions, tour object around Baluran National Park and facilities attractions. In order to obtain data and information for ecotourism demand of tourist and local people characteristic included activity, interest and opinion data were collected through questionnaires and open-ended interviews. The collected data were analyzed by using zonation analysis for ecotorism landscape. Based on the zonation analysis revealed that at Baluran National park obtained 3 zonation that could further develop for ecotourism: (1) mangrove and coral reef ecotourism zonation, (2) savana and forest ecotourism zonation, (3) village ecotourism zonation. Kind of attraction for ecotourism on each zonation are biodiversity of flora and fauna, coral reef, etnobotany information and cultural local people activities.